The Purpose of Implementing the Negative Investment List is to Control Foreign Ownership Domination - Imanuel Koleangan, Garth (Dinasti Research, 2025)
The Negative Investment List (DNI) is a strategic policy of the Indonesian government to regulate foreign ownership limits in certain sectors to protect national economic interests. This policy aims to create a balance between foreign investment and strengthening domestic investors so that strategic sectors remain under national control. To maintain the objectives of the DNI, the government has taken various steps, such as strengthening regulations, providing incentives for local investors, and strict supervision of the implementation of this policy. In addition, the government also encourages the competitiveness of domestic investors through training programs, improving workforce quality, and strategic partnerships with foreign companies in technology transfer and innovation. Periodic evaluation of the effectiveness of the DNI is a key factor in ensuring that this policy remains relevant and can support sustainable national economic growth. With a combination of flexible policies, targeted incentives, and transparency in its implementation, Indonesia can create a conducive investment environment for inclusive and highly competitive economic growth